THE USE OF A DANCE STUDIO IN KNOWING THE LOCAL CULTURE AS SOCIAL SCIENCE LEARNING RESOURCES IN PADEPOKAN SURYA MEDAL PUTERA WIRAHMA STUDIO OF GEGERKALONG, SUKASARI DISTRICT, BANDUNG CITY - Napilah, Siti (Universitas Pendidikan Indonesia, 2019)
This research is motivated by the findings of the researcher that social science learning leaves less room for culture-based learning resources. Moreover, the researcher only came across research references regarding social science learning that raise the issue of internet or museum and the use of a dance studio in introducing the local culture as social science learning resources is yet to be found. The purpose of this research is to explore the utilization of Dance Studio in Padepokan Surya Medal Putera Wirahma of Gegerkalong, Sukasari district, Bandung city as social science learning resources. This research uses a qualitative approach by collecting specific data from the participant, through observation in the dance studio as well as interviews with the dance trainers, the course participants, and the parents of course participants which are supported with documentation. Other than that, the researcher adds expert opinion to strengthen the analysis of the researcher. The research results show that a dance studio plays a role in introducing, strengthening, as well as preserving regional dance. The activities in the studio contain values in the dance, attitudes, and behaviors such as discipline, togetherness, channel interests, motivation, creativity, and the love for the local culture which can be used as learning and be reflected in daily life. The studio that is used as learning resources is quite relevant with the social science material of Junior High School regarding Culture Diversity, Social Institutions, and Efforts to Face Cultural Globalization through visits, observations, and interviews and then the results are made in the form of a report. The use of Padepokan Surya Medal Putera Wirahma may be considered with the driving factors in terms of human resources, studio management, facilitating creativity, as well as support from other parties. Meanwhile, it is important to note that the studio facilities and the timing need to be well-designed so that there are no obstacles in using it as learning resources.